Seasonal and diurnal cycles of surface boundary layer and energy balance in the central andes of peru, mantaro valley - Flores-Rojas, J. L. (2019)
The present study presents a detailed analysis of the diurnal and monthly cycles the surface boundary layer and of surface energy balance in a sparse natural vegetation canopy on Huancayo observatory (12.04° S, 75.32° W, 3313 m ASL), which is located in the central Andes of Peru (Mantaro Valley) during an entire year (May 2018-April 2019). We used a set of meteorological sensors (temperature, relative humidity, wind) installed in a gradient tower 30 m high, a set of radiative sensors to measure all irradiance components, and a set of tensiometers and heat flux plate to measure soil moisture, soil temperatures and soil heat flux. To estimate turbulent energy fluxes (sensible and latent), two flux-gradient methods: the aerodynamic method and the Bowen-ratio energy-balance method were used. The ground heat flux at surface was estimated using a molecular heat transfer equation. The results show minimum mean monthly temperatures and more stable conditions were observed in June and July before sunrise, while maximum mean monthly temperatures in October and November and more unstable conditions in February and March. From May to August inverted water vapor profiles near the surface were observed (more intense in July) at night hours, which indicate a transfer of water vapor as dewfall on the surface. The patterns of wind direction indicate well-defined mountain-valley circulation from south-east to south-west especially in fall-winter months (April-August). The maximum mean monthly sensible heat fluxes were found in June and September while minimum in February and March. Maximum mean monthly latent heat fluxes were found in February and March while minimum in June and July. The surface albedo and the Bowen ratio indicate semi-arid conditions in wet summer months and extreme arid conditions in dry winter months. The comparisons between sensible heat flux (QH) and latent heat flux (QE), estimated by the two methods show a good agreement (R2 above 0.8). The comparison between available energy and the sum of QE and QH fluxes shows a good level of agreement (R2 = 0.86) with important imbalance contributions after sunrise and around noon, probably by advection processes generated by heterogeneities on the surface around the Huancayo observatory and intensified by the mountain-valley circulation. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.